4(x+3)-(-2x+12)=0

Simple and best practice solution for 4(x+3)-(-2x+12)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4(x+3)-(-2x+12)=0 equation:



4(x+3)-(-2x+12)=0
We multiply parentheses
4x-(-2x+12)+12=0
We get rid of parentheses
4x+2x-12+12=0
We add all the numbers together, and all the variables
6x=0
x=0/6
x=0

See similar equations:

| -5(2t+9)=-105 | | 8•x-24=0 | | 4y–12=28 | | 3=r-r-4r+2r+3r+6r | | 2(x-1)-3(5x-6)=250 | | (n+6)(n-5)=102 | | 10x-18=5x+7 | | 7x–2=54 | | 9x-17=8x-7 | | 10x-43=4x-7 | | y/16=0.2 | | 14x+10=22 | | 4z/10+6=7 | | 10x-27=2x-3 | | 6x-7=6x+4 | | 3b+4b=6b+16 | | 5m+37=12 | | 4(3w+10)/5=-7 | | 23=4c-9 | | 3x+7=2(2x-0.5) | | 6(x-2)=33+3x | | 4(x+1)=6(2x+6) | | 2x−3=-1 | | 4x+6=1+14x | | 2x−3=1 | | 2^(2x)-10*2^x+16=0 | | 15-5x=6-8 | | 9x-11=3x+10 | | 7/x−5=6 | | 3e=78-18 | | 5z-3=-48 | | -9x(x+12)=-27 |

Equations solver categories